Inhibition of gap-junctional intercellular communication and activation of mitogen-activated protein kinases by cyanobacterial extracts--indications of novel tumor-promoting cyanotoxins? - Bláha, Luděk; Babica, Pavel; Hilscherová, Klára; Upham, B. L (Toxicon, 2010)
Toxicity and liver tumor promotion of cyanotoxins microcystins have been extensively studied. However, recent studies document that other metabolites present in the complex cyanobacterial water blooms may also have adverse health effects. In this study we used rat liver epithelial stem-like cells (WB-F344) to examine the effects of cyanobacterial extracts on two established markers of tumor promotion, inhibition of gap-junctional intercellular communication (GJIC) and activation of mitogen-activated protein kinases (MAPKs) - ERK1/2. Extracts of cyanobacteria (laboratory cultures of Microcystis aeruginosa and Aphanizomenon flos-aquae and water blooms dominated by these species) inhibited GJIC and activated MAPKs in a dose-dependent manner (effective concentrations ranging 0.5-5mgd.w./mL). Effects were independent of the microcystin content and the strongest responses were elicited by the extracts of Aphanizomenon sp. Neither pure microcystin-LR nor cylindrospermopsin inhibited GJIC or activated MAPKs. Modulations of GJIC and MAPKs appeared to be specific to cyanobacterial extracts since extracts from green alga Chlamydomonas reinhardtii, heterotrophic bacterium Klebsiella terrigena, and isolated bacterial lipopolysaccharides had no comparable effects. Our study provides the first evidence on the existence of unknown cyanobacterial toxic metabolites that affect in vitro biomarkers of tumor promotion, i.e. inhibition of GJIC and activation of MAPKs.
Keywords: Gap Junctions; aktivace enzymů; mikrocystiny; Animals; Cyanobacteria; vztah mezi dávkou a účinkem léčiva; sinice; buněčné linie; Enzyme Activation; Mitogen-Activated Protein Kinases; Aphanizomenon; komplexní směsi; Time Factors; časové faktory; mezerový spoj; Microcystins; Carcinogens; uracil; Cell Line; Fresh Water; Dose-Response Relationship, Drug; fosforylace; karcinogeny; sladká voda; Czech Republic; mitogenem aktivované proteinkinasy; mezibuněčná komunikace; Uracil; krysa rodu Rattus; Česká republika; Cell Communication; zvířata; Complex Mixtures; extracelulárním signálem regulované MAP kinasy; Rats; Phosphorylation; Extracellular Signal-Regulated MAP Kinases